Homology requirements for recombination in Escherichia coli. - Watt, V M (1985)
The DNA sequence homology required for recombination in Escherichia coli has been determined by measuring the recombination frequency between insulin DNA in a miniplasmid pi VX and a homologous sequence in a bacteriophage lambda vector. A minimum of approximately equal to 20 base pairs in a completely homologous segment is required for significant recombination. There is an exponential increase in the frequency of recombination when the length of homologous DNA is increased from 20 base pairs to 74 base pairs and an apparently linear increase with longer DNA segments. Mismatches within a homologous segment can dramatically decrease the frequency of recombination. Thus, the process of recombination is sensitive to the length of precisely base-paired segments between recombining homologues.